Physical Programming for Blind and Low Vision Children at Scale. Issue 5 (1st October 2021) - Morrison, Cecily; Villar, Nicolas; Hadwen-Bennett, Alex; Regan, Tim; Cletheroe, Daniel; Thieme, Anja; Sentance, Sue
Abstract : There is a dearth of appropriate tools for young learners with mixed visual abilities to engage with computational learning. Addressing this gap, Torino is a physical programming language for teaching computational learning to children ages 7–11 regardless of level of vision. To create code, children connect physical instruction pods and tune their parameter dials to create music, audio stories, or poetry. Currently, the uptake of novel educational technologies to support inclusive education of children with disabilities continues to be limited at scale. We consider how the Torino Learning Environment supports non-specialist teachers to teach computational learning to children with mixed visual abilities in a UK-wide evaluation with 75 children and 30 teachers over a period of three months. We demonstrate how children can successfully learn with a novel physical programming language. We articulate how key design constructs such as persistent program overview and liveness supported non-specialist teachers to co-produce learning for children of different ages, visual and cognitive abilities. We conclude with reflective guidance on evaluating inclusive educational technologies at scale. CCS CONCEPTS Human-centered computing → Accessibility → Empirical studies in accessibility